2003
DOI: 10.1002/hbm.10083
|View full text |Cite
|
Sign up to set email alerts
|

Learning of tactile frequency discrimination in humans

Abstract: Learning is based on the remodeling of neural connections in the brain. The purpose of the present study was to examine the extent to which training-induced improvements in tactile frequency discrimination in humans are correlated with an increase of cortical representations in the primary somatosensory cortex. Healthy male subjects (n = 16) were trained in a tactile frequency discrimination task of the left ring finger. During the first 15 days of training, there was a steep improvement in frequency discrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 45 publications
(48 reference statements)
1
20
0
Order By: Relevance
“…In our experiments, the coincidence of task performance with tDCS administration may have served to restrict potentiation effects to the neural populations specifically engaged in crossmodal processing or perceptual learning, leading to the persistent sensitivity improvements. Even extensive practice without brain stimulation can result in improvements in spatial (Wong, Peters, & Goldreich, 2013) and temporal (Imai et al, 2003) touch, so anodal tDCS interventions likely facilitate processing in cortical circuits that typically undergo experience-dependent plasticity. Whether comparable perceptual gains can be achieved with anodal tDCS alone remains to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments, the coincidence of task performance with tDCS administration may have served to restrict potentiation effects to the neural populations specifically engaged in crossmodal processing or perceptual learning, leading to the persistent sensitivity improvements. Even extensive practice without brain stimulation can result in improvements in spatial (Wong, Peters, & Goldreich, 2013) and temporal (Imai et al, 2003) touch, so anodal tDCS interventions likely facilitate processing in cortical circuits that typically undergo experience-dependent plasticity. Whether comparable perceptual gains can be achieved with anodal tDCS alone remains to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Using regular (periodic) and irregular (noisy) vibrations, they showed that in monkeys, activity in SII is best correlated to the discrimination performance. Imai et al (2003) have demonstrated that in humans intensive training of tactile frequency discrimination led to a persistent improvement with the trained and neighboring finger but did not change the primary somatosensory cortical representation as measured with magnetic source imaging, whereas Braun et al (2000) could intriguingly demonstrate that spatial discrimination training led to a differential functional reorganization in SI depending on the difference in the discrimination task.…”
Section: Discussionmentioning
confidence: 96%
“…Presently, it is increasingly proposed that training-related behavioral improvements may be mediated by changes beyond the primary (SI) and secondary (SII) somatosensory cortices (Hodzic et al, 2004;Imai et al, 2003;Karim et al, 2006), thus reinforcing the need for investigations using approaches that are compatible with fMRI techniques. Blood oxygenation-level dependent (BOLD) changes linked to tactile discrimination or learning have been previously explored using a number of innovative paradigms.…”
Section: Potential Applicationsmentioning
confidence: 98%